AI-Generated Text and Its Impact on English Language Creativity: Technological Perspectives and Applications - Deshpande, Shirisha; Vijayalakshmi, A.; Mukherjee, Gitasri; Emimal, M. Samadhanam (Journal of Neonatal Surgery, 2025)
There are serious concerns about the influence of AI on creative expression in the English language, as its fast development has altered the process of text production. Many fields, including creative writing and academic writing, have been impacted by AI-generated content, which is determined by machine learning models and natural language processing (NLP). The impact of AI-generated text on language creativity is investigated in this research, looking at how it might either help or hurt written expression, style, and uniqueness. The report also delves into the science behind AI-generated text and how it's being used in other industries, such as publishing, content development, and education. Despite the convenience and accessibility that AI provides, many are worried about its potential reliance, language homogeneity, and ethical consequences. To better understand how technology might enhance human creativity rather than replace it, the study details the pros and cons of AI-driven writing tools. The results open the door to further investigations on the ethical integration of AI in the fields of language and creativity, and they help us comprehend the active nature of the connection amongst AI, language, and creativity